Assessment of knowledge and practices of Internally Displaced pregnant women attending to antenatal clinic center at Arbat camp in Sulaimani, Kurdistan Region of Iraq - Abdulkhalk Abass, Layla (Kurdistan Journal of Applied Research, 2018)
Internally displaced persons are peoples displaced in it is own country but not crossed a border. After (Islamic State of Iraq and Syria attacked in 2014 to Iraq, millions of Iraqi people flee from their own city war zone to safe camps in Kurdistan region north of Iraq, Arbat camp is one of these camps. Iraqi civilian people constitute most new displacement persons around the world as at least 2.2 million were displaced in 2014. An important part of basic maternal health care is antenatal care that must be provided during pregnancy. Aim of this study is to provide demographic data of Internally Displaced Persons pregnant women and the effect on antenatal care knowledge and practices among of Arbat camp that visits to camp health centers on their health. Assessment of knowledge and practices of pregnant women about antennal care. A cross-sectional descriptive study has been conducted to assess the knowledge and practices of (103) women attended to antenatal care of internally displaced persons) at Arbat camps between 1 January to 30 June 2016. Data collected through the questionnaire form by face-to-face interview. Statistical analyses performed by using SPSS version 16.0, to find descriptive analysis like percentage and frequency and for relative statistical analysis. The results have revealed that most of the pregnant women were in the active reproductive age group 18-25 years old 56(54.4%) pregnant women, housewives 102(99%), illiterate 48(46.6%) pregnant women, were in families that have low income with 48(46.6%) pregnant women with significant relation to the knowledge and practices to antenatal care. In conclusion, most pregnant women have very good knowledge about antenatal care except about performing oral health hygiene during pregnancy. The majority of pregnant women in camps have very good knowledge about all practices that must be do during antenatal except taking medication without a physician prescription.